Fluid overload and length of mechanical ventilation in pediatric sepsis - Winda Paramitha; Rina Triasih; Desy Rusmawatiningtyas (Indonesian Pediatric Society, 2019)
Background Children with sepsis often experience hemodynamic failure and would benefit from fluid resuscitation. On the other hand, critically ill children with sepsis have a higher risk of fluid accumulation due to increased capillary hydrostatic pressure and permeability. Therefore, fluid overload may result in higher morbidity and mortality during pediatric intensive care unit (PICU) hospitalization. Objective To evaluate the correlation between fluid overload and the length of mechanical ventilation in children with sepsis admitted to the PICU. Methods Our retrospective cohort study included children aged 1 month-18 years with sepsis who were admitted to the PICU between January 2013 and June 2018 and mechanically-ventilated. Secondary data was extracted from subjects’ medical records. Data analyses used were independent T-test and survival analysis. Results Of 444 children admitted to the PICU, 166 initially met the inclusion criteria. Of those, 17 children were excluded due to congenital heart disease. Subjects' median age was 19 months and median PELOD-2 score was 8. Eighteen children (12.1%) had positive fluid balance in the first 48 hours. Median mechanical ventilation duration was 5 days. Fluid overload was significantly correlated with length of mechanical ventilation (P=0.01) and PICU mortality (RR=2.06; 95%CI 2.56 to 166; P=0.001). Neither length of PICU stay nor extubation failure were significantly correlated to fluid overload. Conclusion Fluid overload was significantly correlated with length of mechanical ventilation and may be a predictor of mortality in children with sepsis in the PICU.